Crystal Structure Transformations and Dissolution Studies of Cimetidine–Piroxicam Coprecipitates and Physical Mixtures - Tantishaiyakul, Vimon (Springer US, 2009)
We have recently demonstrated that coprecipitation of cimetidine (C) and piroxicam (P) at a mole ratio of 1:1 results in the transformation of the crystalline forms of both drugs to an amorphous state. In this study, coprecipitates and physical mixtures of cimetidine and piroxicam were further investigated at C/P mole ratios of 1:10, 1:5, 1:4, 1:2, 10:1, 20:1, 30:1, 40:1, and 52.5:1, the latter being the composition of a clinically used dosage. The physicochemical properties of these samples were examined using X-ray diffraction and Fourier transform infrared spectroscopy. Additionally, dissolution of piroxicam in the samples at C/P mole ratios of 10:1, 20:1, 30:1, 40:1, and 52.5:1 was investigated at pH 1.2 and pH 4. In coprecipitates with C/P mole ratios of 10:1, 20:1, 30:1, and 40:1, crystalline forms of both drugs were transformed to amorphous states. A mixture of an amorphous state and cimetidine crystalline form A was observed for the coprecipitate with a C/P mole ratio of 52.5:1. For the coprecipitates with C/P mole ratios of 1:2, 1:4, 1:5, and 1:10, cimetidine form A was transformed to form C, whereas piroxicam form II was modified to form I. It is interesting that small molecules, instead of polymers or solvents, can cause such crystal structure transformations. The dissolution of piroxicam at pH 4 is lower than that at pH 1.2. Additionally, the coprecipitates and physical mixtures with C/P mole ratios of 10:1, 20:1, 30:1, 40:1, and 52.5:1 demonstrate substantially higher dissolution of piroxicam compared to that of drug alone.